Development and analysis of Ethylene Glycol/Nanocellulose based Nanofluid Coolant for machining SUS 304 stainless steel - Keeran, Anamalai (2019)
In the manufacturing industry nowadays, machining plays a significant role. When the machining operation is carried out, the temperature rises with the speed and the tool strength decreases, leading to faster wear and tool failure. Thus, it is essential to cool down the heat generated at the tool and work piece interface for a better tool life via effective cooling system. This thesis discusses the effectiveness of Ethylene Glycol/Nanocellulose based Nanofluid Coolant (EGN-NFC) in term of its thermophysical properties such as thermal conductivity and viscosity. Besides that, its’ effectiveness is evaluated and analysed in term of machining performances such as surface roughness, temperature distribution, tool wear, chip formation and tool life during turning machining operation of SUS304 stainless steel through the Box Behnken design of experiment using cemented tungsten-cobalt (WC-Co) coated carbide grade with Ti (C,N) + Al2O3 insert. The effectiveness of the EGN-NFC is compared with the conventional machining coolant which is metal working fluid (MWF). The mathematical model equation for surface roughness was developed using response surface methodology (RSM). The cutting variables are cutting speed, feed rate, and depth of cut. The developed model equations for the surface roughness shows that the most significant input parameter is the feed rate, followed by depth of cut and cutting speed. The turning operation by using EGN-NFC obtains lower surface roughness, achieved greater total length of cut prior to reach the ISO 3865:1977 wear criterion, low temperature distribution and produce discontinuous chip compared with turning operation by using MWF. The cutting tool in turning operation using EGN-NFC take longer time to wear when compare with the one using MWF as the coolant. According to ISO 3865:1977 the wear criteria for turning using MWF reached the maximum total length of cut of 500 mm but the maximum total length of cut for turning using EGN-NFC reached the wear criteria at the cutting distance of 750 mm. The SEM and EDX spectrum shows there are an interfacial layer of nanocellulose from the EGN-NFC embedded and fills the holes in the insert and for a layer which act as an additional protective layer and thermal bridge for the cutting insert. Build-up-edge (BUE), diffusion and adhesion at the cutting edge were the main tool wear mechanism present during turning operation using EGN-NFC. The usage of EGN-NFC in turning operation also helps to reduce the effect of cutting and friction forces during machining operation through discontinuous chip formation results from low cutting temperature. For optimum turning machining performances using EGN-NFC with minimum surface roughness and maximum total length of cut with tool life to be achieved, the parameters been optimized using Minitab to be cutting speed equals to 140 m/min, feed rate equals to 0.05 mm/rev and depth of cut equals to 0.5 mm.